PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS MODEL LEARNING CYCLE 5E PADA PERSAMAAN GARIS LURUS - Kintan Dwi Putri Azura (Jurnal Edukasi dan Penelitian Matematika, 2022)
This research aimed to develop mathematic learning device by using learning cycle 5e model on straight line equation for the eight grade of  junior high school students. The learning device consist of lesson plan and student’s worksheets with five stage of learning cycle namely engagement, exploration, explanation, elaboration, and evaluation. This study used Plomp’s model which consist of three phases, preliminary research, development or prototyping phase, and assesment phase. In the preliminary research conducted analysis of needs, curriculum analysis, concept analysis, and students analysis. In the prototyping phase, the learning device developed with formative evaluation. The study resulted lesson plan has very valid category with validity value 87.5% and very valid category for student’s worksheets with validity value 89.87%. Based on the result, learning devices by using model learning cycle 5e on equation of straight line are valid. Keywords – Learning Device, Learning Cycle 5E, Straight Line Equation, Plomp